2008
DOI: 10.1097/nen.0b013e318187a279
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Protects the Brain Microcirculation From Spirochetal Injury

Abstract: Spirochetal infections are an important cause of neurological disease. In previous studies of the pathogenesis of spirochetal brain infection, mice inoculated with Borrelia turicatae, an agent of tick-borne relapsing fever in North America, developed mild meningitis and parenchymal activation/infiltration by interleukin 10 (IL-10)-producing microglia/macrophages. Here, we investigated the neuro-protective effects of IL-10 during spirochetal infection by comparing the outcomes of B. turicatae infection in wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 46 publications
3
18
1
Order By: Relevance
“…Previously, we had shown that the absence of IL-10 in mice unable to clear peak bacteremia results in rapid death from intracerebral hemorrhage (13,29,52). In this paper, we showed that the same occurs even during relapsing-remitting infection and that HBMEC unable to produce IL-10 are rapidly killed in as few as 20 min of incubation with 10 5 spirochetes/ml.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…Previously, we had shown that the absence of IL-10 in mice unable to clear peak bacteremia results in rapid death from intracerebral hemorrhage (13,29,52). In this paper, we showed that the same occurs even during relapsing-remitting infection and that HBMEC unable to produce IL-10 are rapidly killed in as few as 20 min of incubation with 10 5 spirochetes/ml.…”
Section: Discussionsupporting
confidence: 48%
“…This was the case even after 2-3 mo of persistent infection with 10 7 -10 8 bacteria per ml blood (15,17,18). In contrast, severe cerebrovascular injury developed rapidly following the onset of peak bacteremia in mice deficient in IL-10 and unable to clear the infection (13,19). A fundamentally important protective role of IL-10 for brain endothelium was suspected by the finding of high circulating levels of IL-10 in experimentally infected mice without cerebrovascular injury (13,17) and in patients infected with Borrelia recurrentis with mild clinical disease (20).…”
mentioning
confidence: 89%
See 3 more Smart Citations